Calreticulin Blockade Attenuates Murine Acute Lung Injury by Inducing Polarization of M2 Subtype Macrophages - Jiang, Zhilong; Chen, Zhihong; Hu, Lu; Qiu, Lin; Zhu, Lei (Frontiers in Immunology, 2020)
Calreticulin (CALR) has anti-tumor effects by increasing dendritic cell maturation and tumor antigen presentation. However, whether CALR affects macrophages and modulates progression of acute respiratory distress syndrome/acute lung injury (ARDS/ALI) remains unknown. In this study, we discovered that CALR protein was highly expressed in the mice with LPS-induced ALI and CALR expression level was positively correlated to the severity of ALI. Commercial anti-CALR antibody (aCALR) can neutralize recombinant CALR (rCALR) and suppress the expression of TNF-alpha and IL-6 in the rCALR-treated macrophages. Blocking CALR activity by intraperitoneal (i.p.) administration of aCALR significantly suppressed ALI, accompanied with lower total cell counts, neutrophil and T cell infiltration in bronchoalveolar lavage (BAL) and lung tissues. The expression of CXCL15, IL-6, IL-1beta, TNF-alpha and CALR were significantly reduced, in association with more polarization of Siglec F+CD206+ M2 subtype macrophages in the aCALR-treated mice. Pre-depletion of circulating monocytes did not abolish the aCALR-mediated suppression of ALI. Further analysis in bone marrow-derived macrophages (BMDMs) showed that aCALR suppressed the expression of CD80, IL-6, IL-1beta, IL-18, NLRP3 and p-p38 MAPK; but enhanced the expression of CD206 and IL-10. In addition, we observed more expression and phosphorylation of STAT6 in the aCALR-treated BMDM. Lack of STAT6 resulted in comparable and slightly higher expression of CALR, TNF-alpha and IL-6 in the aCALR-treated STAT6-/- BMDMs than the untreated cells. Therefore, we conclude that CALR is a novel biomarker in the evaluation of ALI. Blocking CALR activity by aCALR effectively suppressed ALI independent of circulating monocytes. Siglec F+CD206+ M2 subtype macrophages and p38 MAPK/STAT6 signaling pathway played important role in the immune regulation of aCALR. Blocking CALR activity is a promising therapeutic approach in the treatment of ARDS/ALI.